The best dance moves in the world... ever! 100 new and classic moves and how to bust them - Pagett, Matt. (Singapore Page One Publishing, 2007)
An illustrated, step-by-step guide to one hundred new and classic dance moves features detailed instructions for the Robot, Running Man, Hustle, Funky Chicken, Moonwalk, Cabbage Patch, Smurf, and many other dances, accompanied by tips on suitable music and special advice for each dance.
Includes index.
Keywords: Modern dance; Dance